CURRENT TRENDS IN STARTUP FINANCING: OPPORTUNITIES, CHALLENGES, AND EMERGING FUNDING MODELS - Shaymardanova Mohidil Mansurovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Startup companies play a crucial role in driving innovation, economic growth, and job creation in the modern economy. However, access to financial resources remains one of the most significant challenges faced by startups, particularly during the early stages of development. In recent years, startup financing has undergone substantial transformation due to technological advancements, globalization, and the emergence of alternative funding mechanisms. Traditional funding sources such as bank loans and venture capital are increasingly complemented by crowdfunding, angel investment, accelerators, incubators, and government support programs. This theoretical review examines contemporary startup financing models, analyzes their advantages and limitations, and explores emerging trends shaping entrepreneurial ecosystems worldwide. The findings indicate that diversified funding opportunities have improved access to capital for entrepreneurs; however, challenges related to investment risks, market uncertainty, and financial sustainability continue to affect startup growth. The study concludes that successful startup financing requires strategic planning, financial literacy, and an understanding of evolving investment landscapes.